Managing Attribute—Value Clinical Trials Data Using the ACT/DB Client—Server Database System - Nadkarni, Prakash M. (American Medical Informatics Association, 1998)
ACT/DB is a client—server database application for storing clinical trials and outcomes data, which is currently undergoing initial pilot use. It stores most of its data in entity—attribute—value form. Such data are segregated according to data type to allow indexing by value when possible, and binary large object data are managed in the same way as other data. ACT/DB lets an investigator design a study rapidly by defining the parameters (or attributes) that are to be gathered, as well as their logical grouping for purposes of display and data entry. ACT/DB generates customizable data entry. The data can be viewed through several standard reports as well as exported as text to external analysis programs. ACT/DB is designed to encourage reuse of parameters across multiple studies and has facilities for dictionary search and maintenance. It uses a Microsoft Access client running on Windows 95 machines, which communicates with an Oracle server running on a UNIX platform. ACT/DB is being used to manage the data for seven studies in its initial deployment.